2015
DOI: 10.1097/nen.0000000000000226
|View full text |Cite
|
Sign up to set email alerts
|

BRAF Fusion Analysis in Pilocytic Astrocytomas: KIAA1549-BRAF 15-9 Fusions Are More Frequent in the Midline Than Within the Cerebellum

Abstract: Pilocytic astrocytomas (PAs) are increasingly tested for KIAA1549-BRAF fusions. We used reverse transcription polymerase chain reaction for the 3 most common KIAA1549-BRAF fusions, together with BRAF V600E and histone H3.3 K27M analyses to identify relationships of these molecular characteristics with clinical features in a cohort of 32 PA patients. In this group, the overall BRAF fusion detection rate was 24 (75%). Ten (42%) of the 24 had the 16-9 fusion, 8 (33%) had only the 15-9 fusion, and 1 (4%) of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 30 publications
4
36
1
Order By: Relevance
“…The mutation is also detected in about two-thirds of pleomorphic xanthoastrocytomas (PXA), one-third of gangliogliomas (GG) and 20%-25% of dysembryoplastic neuroepithelial tumors (DNT) (Becker et al, 2015;Chappé et al, 2013;Dias-Santagata et al, 2011;Ichimura, Nishikawa, & Matsutani, 2012;Jones et al, 2008;Koelsche et al, 2013;Rodriguez, Lim, Bowers, & Eberhart, 2013;Roth et al, 2015). Moreover, pilocytic astrocytoma (PA) is characterized by a fusion between the BRAF gene and the locus KIAA1549 (chromosome 7q34) (Faulkner et al, 2015;Jones et al, 2008;Roth et al, 2015). The fusion causes a constitutional activation of the tyrosine kinase domain of BRAF and a permanent activation of the MAP kinase pathway (MAPK) (Roth et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutation is also detected in about two-thirds of pleomorphic xanthoastrocytomas (PXA), one-third of gangliogliomas (GG) and 20%-25% of dysembryoplastic neuroepithelial tumors (DNT) (Becker et al, 2015;Chappé et al, 2013;Dias-Santagata et al, 2011;Ichimura, Nishikawa, & Matsutani, 2012;Jones et al, 2008;Koelsche et al, 2013;Rodriguez, Lim, Bowers, & Eberhart, 2013;Roth et al, 2015). Moreover, pilocytic astrocytoma (PA) is characterized by a fusion between the BRAF gene and the locus KIAA1549 (chromosome 7q34) (Faulkner et al, 2015;Jones et al, 2008;Roth et al, 2015). The fusion causes a constitutional activation of the tyrosine kinase domain of BRAF and a permanent activation of the MAP kinase pathway (MAPK) (Roth et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The fusion causes a constitutional activation of the tyrosine kinase domain of BRAF and a permanent activation of the MAP kinase pathway (MAPK) (Roth et al, 2015). Of interest, cerebellar PA harbor the BRAF fusion in about 80% of cases while supratentorial (hemispheric) PA present with the fusion in 29% of cases and with the BRAF-V600E mutation in about 5% of cases (Becker et al, 2015;Faulkner et al, 2015;Ichimura et al, 2012;Jones et al, 2008;Rodriguez et al, 2013). Distinguishing those circumscribed GNT, characterized by an overall favorable prognosis, from diffuse gliomas (diffuse astrocytomas, oligodendrogliomas), that present a dismal prognosis, may be difficult by histopathology alone.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of fusion transcripts was further confirmed in four cases tested by RT-PCR. In two cases, exon 15 of KIAA1549 was fused to exon 9 of BRAF (15-9), which is also commonly seen in extra-cerebellar midline PAs [2]. The 15-11 fusion seen in case #3 is occasionally found in supratentorial PAs [5].…”
mentioning
confidence: 99%
“…The detection of KIAA1549-BRAF fusions with their specific breakpoints is important in clinical settings (13). The identification of the type of fusion present is important for prognosis; therefore, any diagnostic method implemented should provide this information (15). We achieved this using the Pyromark system.…”
Section: Discussionmentioning
confidence: 99%
“…This method can be used for shorter sequences than direct sequencing methods, but the technique has been shown to be accurate and reproducible enough to detect fusion genes (12). Chromosomal rearrangements caused by fusion genes are common in brain tumours (13)(14)(15); the KIAA1549 exon-15v-raf murine sarcoma viral oncogene homolog B1 (BRAF) exon-9 (KIAA1549-BRAF) fusion, is considered a driver of genetic events and a diagnostic marker (13), particularly in pilocytic astrocytoma, a major type of paediatric brain tumour (15). Studies have revealed that specific breakpoints of KIAA1549-BRAF correlate with tumour characteristics of different types of brain tumour (14).…”
mentioning
confidence: 99%